The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.biochem.0c00629
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for the Treatment of Pain: Chemistry and Pharmacology of Salvinorin A, Mitragynine, and Collybolide

Abstract: Pain remains a very pervasive problem throughout medicine. Classical pain management is achieved through the use of opiates belonging to the mu opioid receptor (MOR) class, which have significant side effects that hinder their utility. Pharmacologists have been trying to develop opioids devoid of side effects since the isolation of morphine from papaver somniferum, more commonly known as opium by Sertürner in 1804. The natural products salvinorin A, mitragynine, and collybolide represent three nonmorphinan na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 170 publications
2
50
0
Order By: Relevance
“…It is important to note, however, that TRV130 displays weak G-protein bias in vitro ( Schmid et al, 2017 ) and mixed safety results in rodent models ( Austin Zamarripa et al, 2018 ; Altarifi et al, 2017 ). Other MOR ligands with greater bias, such as SR17018 ( Schmid et al, 2017 ), show diminished respiratory depression in rodents compared to fentanyl ( Gillis et al, 2020a ), while PZM21 ( Manglik et al, 2016 ; Kudla et al, 2019 ) and mitragynine(s) ( Váradi et al, 2016 ; Kruegel et al, 2016 ; Kruegel et al, 2019 ; Chakraborty and Majumdar, 2020 ) display reduced abuse liability ( Yue et al, 2018 ; Hemby et al, 2019 ). Similarly, some KOR-selective G protein biased ligands such as HS666 ( Spetea et al, 2017 ), 6′GNTI ( Rives et al, 2012 ), and triazole 1.1 ( Brust et al, 2016 ) show a promising separation of place aversion from analgesia, unlike balanced KOR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that TRV130 displays weak G-protein bias in vitro ( Schmid et al, 2017 ) and mixed safety results in rodent models ( Austin Zamarripa et al, 2018 ; Altarifi et al, 2017 ). Other MOR ligands with greater bias, such as SR17018 ( Schmid et al, 2017 ), show diminished respiratory depression in rodents compared to fentanyl ( Gillis et al, 2020a ), while PZM21 ( Manglik et al, 2016 ; Kudla et al, 2019 ) and mitragynine(s) ( Váradi et al, 2016 ; Kruegel et al, 2016 ; Kruegel et al, 2019 ; Chakraborty and Majumdar, 2020 ) display reduced abuse liability ( Yue et al, 2018 ; Hemby et al, 2019 ). Similarly, some KOR-selective G protein biased ligands such as HS666 ( Spetea et al, 2017 ), 6′GNTI ( Rives et al, 2012 ), and triazole 1.1 ( Brust et al, 2016 ) show a promising separation of place aversion from analgesia, unlike balanced KOR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that systemic injections of the kratom extract and kratom alkaloids (7-hydroxymitragynine, paynantheine, speciogynine, and mitragynine) decrease voluntary alcohol drinking in mouse models of moderate and binge alcohol consumption, with the kratom alkaloid 7-hydroxymitragynine being the most efficacious ( Gutridge et al, 2020 ). Kratom alkaloids differ from opium-derived opioids and clinically used synthetic opioids in that upon binding to opioid receptors they activate the Gα i/o protein, without promoting β-arrestin recruitment to the receptor ( Kruegel et al, 2016 ; Váradi et al, 2016 ; Faouzi et al, 2020 ; Chakraborty and Majumdar, 2021 ). Several preclinical studies in mice strongly suggest that β-arrestin recruitment at the delta opioid receptor (δOR) is a liability for enhanced alcohol use and should be avoided ( Chiang et al, 2016 ; Robins et al, 2018 ; Gutridge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The major active alkaloid found in kratom is mitragynine, along with more than 40 other minor alkaloids. [11][12][13][14][15][16] In recent years, we have become interested in the chemistry and pharmacology of kratom alkaloids as probes to understand opioid receptor function. 11,[17][18][19][20][21][22][23] Previous reports from our group reported that mitragynine (possessing an indole core), its oxidation product 7OH (possessing an indolenine core), and mitragynine pseudoindoxyl (MP, a skeletal rearrangement product of 7OH with a spiro-pseudoindoxyl core) (Figure 1A), are all opioid antinociceptive agents 18,19 and Gprotein biased MOR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] In recent years, we have become interested in the chemistry and pharmacology of kratom alkaloids as probes to understand opioid receptor function. 11,[17][18][19][20][21][22][23] Previous reports from our group reported that mitragynine (possessing an indole core), its oxidation product 7OH (possessing an indolenine core), and mitragynine pseudoindoxyl (MP, a skeletal rearrangement product of 7OH with a spiro-pseudoindoxyl core) (Figure 1A), are all opioid antinociceptive agents 18,19 and Gprotein biased MOR agonists. 17,18,20,22 We also reported oxidative metabolism of mitragynine to 7OH mitragynine using a CYP3A-mediated pathway following oral administration of mitragynine in mice.…”
Section: Introductionmentioning
confidence: 99%